Using Cue Cards to Improve EFL Students’ Writing Skills - Syaiban Abdul Kamil; Rofiqoh Rofiqoh; Muhammad Arid; Budi Budi (Journal of General Education and Humanities, 2026)
Writing remains a significant challenge for EFL students, and the use of instructional media is a recognized strategy to address this issue. This study investigated the efficacy of cue cards in improving the writing skills of tenth-grade students at SMA Negeri 2 Palu. Employing a quasi-experimental design, the study utilized a population of 366 students, with a sample of 63 students selected through purposive sampling: 31 students in class X-I (experimental group) and 32 students in class X-J (control group). The research instrument was a writing test focused on descriptive text. Because the data were not normally distributed, a non-parametric Mann-Whitney U test was applied using SPSS. The results revealed a post-test p-value of 0.001, which is significantly lower than the 0.05 alpha level. This indicates a statistically significant difference between the two groups following the treatment, confirming that cue card media effectively improves EFL students’ writing skills. Consequently, this media is recommended as a valuable tool for enhancing classroom instruction.